2012
DOI: 10.1002/pros.22572
|View full text |Cite
|
Sign up to set email alerts
|

Expression differences of circulating microRNAs in metastatic castration resistant prostate cancer and low‐risk, localized prostate cancer

Abstract: Background Recent studies show that microRNAs (miRNAs), small non-coding RNAs that negatively regulate gene expression, may have potential for monitoring cancer status. We investigated circulating miRNAs in prostate cancer that may be associated with the progression of hormone-sensitive primary tumors to metastatic castration resistant prostate cancer (CRPC) after androgen deprivation therapy. Methods Using genome-wide expression profiling by TaqMan Human MicroRNA Arrays (Applied Biosystems) and/or quantitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
185
2
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 228 publications
(207 citation statements)
references
References 25 publications
18
185
2
2
Order By: Relevance
“…This increase in miR-375 was initially reported in our earlier study (5), as well as by Schaefer and colleagues (24) and Martens-Uzunova and colleagues (25). Two recent studies reported increased serum levels of miR-375 (and miR-141) in patients with metastatic prostate carcinoma (26,27). In contrast, a miRNA profiling approach based on high-throughput sequencing by Watahiki and colleagues did not find an increase of miR-375 in metastatic prostate carcinoma (28).…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…This increase in miR-375 was initially reported in our earlier study (5), as well as by Schaefer and colleagues (24) and Martens-Uzunova and colleagues (25). Two recent studies reported increased serum levels of miR-375 (and miR-141) in patients with metastatic prostate carcinoma (26,27). In contrast, a miRNA profiling approach based on high-throughput sequencing by Watahiki and colleagues did not find an increase of miR-375 in metastatic prostate carcinoma (28).…”
Section: Discussionsupporting
confidence: 61%
“…Recent data also describe elevated serum levels of miR-375 and miR-141 as predictors for poor prognosis (27) or metastasis (26) reviewed in reference 6. MiR-141 is found upregulated in primary tissues in a variety of studies including ours (2,25), and inclusion of miRNA expression data significantly improves the accuracy of markers like prostatespecific antigen in the diagnosis or prediction of tumor outcome (33).…”
Section: Discussionmentioning
confidence: 99%
“…121,126 In nine out of these 15 miR-141-studies, miR-141 was only evaluated as a marker of advanced or metastatic prostate cancer (Table 3). 20,84,96,99,101,103,[113][114][115] but was frequently, if at all reported, not better than the routine marker PSA. 114,115,118 These data underline the fact that the clinical relevance of a marker can only be truly assessed if studies with similar questions are compared: a useful diagnostic marker might be a useless prognostic marker and vice versa.…”
Section: [H1] Biofluid Mirnas In Prostate Cancermentioning
confidence: 93%
“…An example of this are the miR-141 and miR-375, which have been detected at significantly greater levels in metastatic compared to non-metastatic prostate cancer. 8,9 Although investigating the transcriptome can provide some valuable insight into biology (phenotype), the socalled machinery driving the biology of the cell and organism are the proteins (the proteome). The link between transcriptional activity and the proteome is not necessarily direct, and so the definition of the biology and the identification of drivers of disease and therapeutic resistance require multiple omics-based approaches.…”
Section: Introductionmentioning
confidence: 99%